The variety of clinical presentations in IgG4-related disease in Rheumatology - Sebastian, Agata (Rheumatol Int, 2017)
IgG4-related disease (IgG4-RD) belongs to the group of rare diseases in which the identification of the characteristic histology and immunohistochemistry provides with the gold standard in the diagnosis. The variable organ dysfunction reflects the clinical presentation. The examples of different IgG4-RD presentations in the Rheumatology Unit were discussed in this article. The spectrum of IgG4-RD is wide-ranging and manifested in one or more organs synchronously or metachronously. In the presented article, we described five different cases of IgG4-RD. Four cases were reaffirmed in the histopathological assessment. The clinical and laboratory findings were analyzed and the assigned therapy was discussed. According to our experience, the diagnosis of IgG4-RD requires the careful clinicopathological correlation. The diagnosis relies on the coexistence of various clinical, laboratory, radiological, and histopathological findings, although none of them is pathognomonic itself. The time needed for the diagnosis and variety of clinical forms of IgG4-RD shows that there is need of the cooperation among many specialists for the better and earlier recognition of the disease.